Design, Simulation and Fabrication of a Slot Loaded 2.45 GHz Microstrip Patch Antenna for ISM Band Wireless Applications - Samuel O. OLADIPUPO; Dominic S. NYITAMEN; Lanre S. MOJEREOLA (FUDMA Journal of Engineering and Technology, 2026)
Due to an exponential increase in wireless devices in recent time, there is demand for development of low cost, low profile, less weight, highly reliable antennas which is backbone of any effective wireless devices. This paper presents the design, simulation, fabrication, and experimental validation of a slot loaded 2.45GHz microstrip patch antenna intended for Industrial, Scientific, and Medical (ISM) band applications. A new compact edge slot antenna was designed using conventional transmission line theory and implemented on an FR-4 substrate of relative permittivity of 4.4 and thickness of 1.6mm. Computer Simulation Technology (CST) was employed to model and optimize the antenna for enhancement of the antenna. The proposed antenna was fabricated by chemical etching method using FeCl3 as the etchant. The fabricated prototype was tested using a Vector Network Analyzer (miniVNA tiny 1 - 3GHz) to validate simulated results. The simulation results obtained were; resonant frequency is 2.45GHz with a return loss is –37.506 dB, bandwidth is 106.67MHz, VSWR is 1.03, gain is 5.04dB and radiation efficiency of 52.7 %. While the measured results of the fabricated antenna were; resonant frequency is 2.5GHz with a return loss of –27.21dB, bandwidth of 80.75MHz, and VSWR is 1.09, these results are good enough for the proposed antenna to be suitable for ISM band wireless applications such as Wi-Fi, Bluetooth, and IoT devices.
Keywords: Microstrip patch antenna (MPA), 2.45 GHz, ISM band, CST simulation, Internet of Things (IoT).